Managing tourism and hospitality services : theory and international applications - Prideaux, B. (Bruce); Moscardo, Gianna; Laws, Eric, 1945- (CABI, 2006)
This book aims to enhance theoretical and practical understanding of quality management in tourism and hospitality. Part I (chapters 1-5) deals with the core issue of managing customer satisfaction. Part II (chapters 6-8) focuses on structural issues, particularly competition and collaboration, both of which are strongly characteristic of the industry. Part III (chapters 9-14) builds on the understanding of customer satisfaction and the functioning of industry relationships by reporting and critically analysing examples of improvements to specific tourism and hospitality services. Part IV (chapters 15-20) focuses on the experiences of those who work in the industry, their interactions with clients, and ways of managing them more effectively. Part V (chapters 21-27) focuses on methods in researching tourism and hospitality service management. Part VI (chapter 28) concludes the book. There is a subject index.